CORPORATE GOVERNANCE AND AUDITOR OPINION: PORTUGUESE EVIDENCE (2008-2011) - Santos, Marília Medeiros (2015)
This paper analysed the effect of ownership structure in the audit opinions as well as the effect of some corporate governance characteristics in the audit opinions. To fulfil this objective we used a logistic regression, considering a sample of non-financial Portuguese listed companies on the Euronext Lisbon for the period between 2008 and 2011. Our results showed that the concentration of ownership, the independence of the board, the presence of an audit committee and the liquidity ratio influence positively the audit opinion, promoting more reliable financial information. In the Portuguese context, the results do not generate, overall, the effect documented by the theoretical frameworks of government of Anglo-Saxon societies. However, this study contributes to a better understanding and interest in this line of research, since this is a current topic, and an under-researched topic in Portugal.